1836 Miss. Rev. Stat. 453 - (:unkn) unknown (My University, 1836)
Ch. 19, tit. 10, art. 2, § 3: No person shall fire or discharge any gun, pistol, rockets, squib, cracker, or other firework, within a quarter of a mile of any building, on the twenty-fifth day of December, on the last day of December, on the first day of January, or on the twenty-second day of February, in any year; nor on the fourth day of July or such other day as shall at any time be celebrated as the anniversary of American independence
Keywords: DISCHARGE